2022
DOI: 10.1016/j.jbc.2021.101475
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function characterization of the mono- and diheme forms of MhuD, a noncanonical heme oxygenase from Mycobacterium tuberculosis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Mycobacterium tuberculosis (MTB) infection causes acute oxidative stress and increases the expression of HO-1, which may in turn facilitate MTB survival and growth due to increased iron availability. [75][76][77] MhuD is a noncanonical heme oxygenase (HO) from M. tuberculosis (Mtb) that catalyzes unique heme degradation chemistry distinct from canonical HOs, generating mycobilin products without releasing carbon monoxide. [75][76][77] Its crucial role in the Mtb heme uptake pathway has identified MhuD as an auspicious drug target.…”
Section: Biosynthesis Of Coenzyme F420 In M Tuberculosis and Drug Res...mentioning
confidence: 99%
See 2 more Smart Citations
“…Mycobacterium tuberculosis (MTB) infection causes acute oxidative stress and increases the expression of HO-1, which may in turn facilitate MTB survival and growth due to increased iron availability. [75][76][77] MhuD is a noncanonical heme oxygenase (HO) from M. tuberculosis (Mtb) that catalyzes unique heme degradation chemistry distinct from canonical HOs, generating mycobilin products without releasing carbon monoxide. [75][76][77] Its crucial role in the Mtb heme uptake pathway has identified MhuD as an auspicious drug target.…”
Section: Biosynthesis Of Coenzyme F420 In M Tuberculosis and Drug Res...mentioning
confidence: 99%
“…[75][76][77] MhuD is a noncanonical heme oxygenase (HO) from M. tuberculosis (Mtb) that catalyzes unique heme degradation chemistry distinct from canonical HOs, generating mycobilin products without releasing carbon monoxide. [75][76][77] Its crucial role in the Mtb heme uptake pathway has identified MhuD as an auspicious drug target. MhuD is capable of binding either one or two hemes within a single active site.…”
Section: Biosynthesis Of Coenzyme F420 In M Tuberculosis and Drug Res...mentioning
confidence: 99%
See 1 more Smart Citation
“…MhuD of M. tuberculosis can bind one or two molecules of heme at the same active site, whereas IsdG/I just binds a single heme at an active site [ 73 ]. Both diheme-MhuD and monoheme-MhuD complexes are enzymatically active and are able to degrade heme [ 78 ]. IsdG-like proteins have also been identified in S. epidermidis [ 79 ], B. anthracis [ 80 ], and L. monocytogenes [ 81 ].…”
Section: Strategies Of Gram-positive Bacteria To Resist Heme Toxicitymentioning
confidence: 99%
“…Both FecB and FecB2 constructs with hexa-histidine (His) tags have high nanomolar to micromolar affinities to heme, 1.20 ± 0.10 μM and 0.87 ± 0.06 μM, respectively (S5 Fig and Table 2). Previous studies have shown that His tags can interfere with heme binding studies [50][51][52], thus we determined the affinity of heme to FecB and FecB2 in the absence of a His tag (Figs 4 and S5). For FecB, the affinity for heme was similar in the presence or absence of the His tag.…”
Section: Determination Of Potential Substrates Of Fecb and Fecb2mentioning
confidence: 99%